2021
DOI: 10.3390/plants10091930
|View full text |Cite
|
Sign up to set email alerts
|

Incorporated Biochar-Based Soil Amendment and Exogenous Glycine Betaine Foliar Application Ameliorate Rice (Oryza sativa L.) Tolerance and Resilience to Osmotic Stress

Abstract: Osmotic stress is a major physiologic dysfunction that alters the water movement across the cell membrane. Soil salinity and water stress are major causal factors of osmotic stress that severely affect agricultural productivity and sustainability. Herein, we suggested and evaluated the impact of integrated biochar-based soil amendment and exogenous glycine betaine application on the growth, physiology, productivity, grain quality, and osmotic stress tolerance of rice (Oryza sativa L., cv. Sakha 105) grown in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Electrolyte leakage was determined according to Hafez et al [33]. In total, 0.2 g root material was washed in deionized water and then surface moisture was wiped off.…”
Section: Physiological Measurement Of Wheat Roots Under High Temperat...mentioning
confidence: 99%
“…Electrolyte leakage was determined according to Hafez et al [33]. In total, 0.2 g root material was washed in deionized water and then surface moisture was wiped off.…”
Section: Physiological Measurement Of Wheat Roots Under High Temperat...mentioning
confidence: 99%
“…Moreover, this production should be increased to cope with continuing population growth and the threat of environmental pressures [ 5 ]. Drought stress is a harsh environmental factor with devastating impacts on global rice production [ 6 , 7 ]. Nearly half the cultivated area of rice worldwide is predicted to suffer from water shortages, causing a substantial reduction in rice yield [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These changes in soil properties associated with biochar amendment can thus influence enzyme activities. In the literature, several studies have reported that the application of biochar significantly improved the antioxidant enzyme contents, e.g., superoxide dismutase (SOD), peroxidase (POD) and ascorbate peroxidase (APX) together with a decrease in reactive oxygen species (ROS), e.g., malondialdehyde (MDA), and electrolyte leakage (EL) in plants under stress conditions [16]. In a recent study, Zhang et al [8] revealed that the soil amendments with biochar increased antioxidant enzyme activity and decreased the MDA content in sugar beet (Beta vulgaris L.) under stress conditions.…”
Section: Introductionmentioning
confidence: 99%